A facilitated approach to family case conferencing for people with advanced dementia living in nursing homes: perceptions of palliative care planning coordinators and other health professionals in the IDEAL study. (27th June 2017) - Luckett, Tim; Chenoweth, Lynnette; Phillips, Jane; Brooks, Deborah; Cook, Janet; Mitchell, Geoffrey; Pond, Dimity; Davidson, Patricia M.; Beattie, Elizabeth; Luscombe, Georgina; Goodall, Stephen; Fischer, Thomas; et al.
ABSTRACT: Background: Palliative care for nursing home residents with advanced dementia is often sub-optimal due to poor communication and limited care planning. In a cluster randomized controlled trial, registered nurses (RNs) from 10 nursing homes were trained and funded to work as Palliative Care Planning Coordinators (PCPCs) to organize family case conferences and mentor staff. This qualitative sub-study aimed to explore PCPC and health professional perceptions of the benefits of facilitated case conferencing and identify factors influencing implementation. Method: Semi-structured interviews were conducted with the RNs in the PCPC role, other members of nursing home staff, and physicians who participated in case conferences. Analysis was conducted by two researchers using a thematic framework approach. Results: Interviews were conducted with 11 PCPCs, 18 other nurses, eight allied health workers, and three physicians. Perceived benefits of facilitated case conferencing included better communication between staff and families, greater multi-disciplinary involvement in case conferences and care planning, and improved staff attitudes and capabilities for dementia palliative care. Key factors influencing implementation included: staffing levels and time; support from management, staff and physicians; and positive family feedback. Conclusion: The facilitated approach explored in this study addressed known barriers to case conferencing. However, current business models in the sector make it difficult for case conferencing to receive the required levels of nursing qualification, training, and time. A collaborative nursing home culture and ongoing relationships with health professionals are also prerequisites for success. Further studies should document resident and family perceptions to harness consumer advocacy.